CLINICAL MANIFESTATION OF BMI, TLC, ALBUMIN AND CD4 AFTER PROVISION OF SNAKEHEAD NUGGET AND COLORED FRUIT JUICE TO PEOPLE WITH HIV - Ngena Ria; Ginta Siahaan; Zuraidah Nasution; Hanna Sriyanti Saragih (Media Gizi Indonesia, 2022)
Snakehead fish has high content of zinc and albumin, it can be given to people with immune disorder. Snakehead fish can be made into various kind of food product that are high in nutrients, have aestetic value, and taste like nugget. The effectiveness of zinc and albumin function can work optimally when the consumption is combined with food ingredient that are high in bioactive substances such as lycopene, anthocyanin, flavonoid, karetonoid, bromelain, papain and quercetin. The purpose of this study was to analyze the effectof snakehead nugget administration and colored fruit juices simultaneously on clinical manifestation, BMI, TLC, albumin and CD4 value in PLHIV at HIV/AIDS Rehabilitation Center in Medan.  The design of research was quasy experimental with pre and post test design. The subjects was 40 people who lived at HIV/AIDS Rehabilitation Center in Medan and given snackhead fish nugget and colored fruit juice for 24 days. The data analysis used dependent T-test, after data normality test had previously been carried out. There was effect before and after administration of snakehead fish nuggets and colored fruit juice on clinical manifestation, BMI, TLC and CD4 levels with p value <0.05. It is necessary to provide treatment in  longer term as preventive measure for the emergence of various clinical manifestations as well as to increase BMI, TLC, albumin and CD4 in PLHIV at HIV/AIDS Rehabilitation Center in Medan.